Exploring Alcohol Use and IPV Among Couples Presenting to Couple Therapy: A Brief Note - Patton, Rikki (Journal of interpersonal violence, 2021)
Prior research has indicated the significant overlap between risky alcohol use and intimate partner violence (IPV) among couples. However, few studies have explicitly examined the intersection of alcohol use and IPV among distressed couples (e.g., couples seeking couples therapy). The current study aimed to (a) examine how couples presenting to couple therapy experience alcohol use, IPV, and the co-occurrence of both alcohol use and IPV and (b) the effect of the intersection of alcohol use and IPV in couples on relational functioning. Archival data collected from 71 couples presenting to couple therapy at a University training clinic were used to explore the research aims. Data analysis procedures included univariate statistics to characterize the sample and bivariate statistics to examine the research aims. Findings indicated that 16.9% of couples screened positive for both alcohol use and IPV and that there were significant group differences in relational functioning among females in the sample. These findings indicate the potential need for universal alcohol and IPV screening among clinicians working with couples.